Experimental study on a nonlinear vibration isolator based on a post-buckled inverted L-shaped beam - Takumi SASAKI; Timothy WATERS; Yumiko TSUJI (Mechanical Engineering Journal, 2015)
In this paper, the characteristics and the effectiveness of a nonlinear passive vibration isolator based on a post-buckled beam is investigated experimentally. The intended application is specifically isolation in the vertical direction where the isolator is required to be sufficiently stiff statically to bear the weight of the isolated mass. The isolator consists of two beams joined to form an inverted L-shape and the weight of the isolated mass is taken to act at the vertex. If the weight of isolated mass is larger than the buckling load of the L-shaped beam then the beam buckles in one of two modes, one of which is unstable. In this paper, the static restoring force of the unstable mode is measured and an appropriately selected coil spring is added to counteract the negative stiffness of the beam. The resulting system presents a dramatically lower stiffness to small excursions about its equilibrium position in its buckled state but maintains its static load bearing capability. Free vibration measurements are presented which show some amplitude dependency of the natural frequency for large amplitude motion. Low amplitude harmonic base excitation measurements are also conducted from which transmissibility measurements are obtained and compared with corresponding results from a Finite Element model. The fundamental resonance is about 80% lower than that achievable by a comparable linear isolator. However the potential improvement in isolation performance has not been fully realised in the prototype design due to the presence of higher frequency internal resonances of the isolator, mitigation of which is the focus of ongoing work.